PENERAPAN FUZZY INFERENCE SYSTEM SUGENO DALAM MENENTUKAN PENYALURAN PEMBIAYAAN RAHN - Rahmawati, Rahmawati; Nurjannah, Nurjannah; Rahma, Ade Novia; zukrianto, zukrianto (Math Educa Journal, 2021)
The price of gold and the inflation rate are some of the right indicators to analyze the development of sharia rahn mortgage financing distribution. This study aims to determine the amount of rahn financing distribution based on the average gold price of pawnshops and Indonesia's inflation rate in 2018-2019. In this study, Sugeno's fuzzy inference system (FIS) method was used to determine the amount of Rahn's financing distribution. The steps used in the FIS Sugeno method are the formation of fuzzy sets, application of implication and affirmation functions (defuzzification). Based on the FIS Sugeno method, the results of the calculation of the total distribution of rahn financing of PT. Pegadaian (Persero) Branch Syariah Subrantas Pekanbaru in January 2018 was obtained at 252.642.105 with an accuracy value of 89.44%.